Transformation Mechanism of Rare Ginsenosides in American Ginseng by Different Processing Methods and Antitumour Effects - Li, Zhi-man; Shao, Zi-jun; Qu, Di; Huo, Xiao-hui; Hua, Mei; Chen, Jian-bo; Lu, Yu-shun; Sha, Ji-Yue; Li, Shan-shan; Sun, Yin-shi (Frontiers in Nutrition, 2022)
The mechanism by which ginsenosides from Panax quinquefolium L. transform into rare saponins by different processing methods and their antitumour effects have yet to be fully elucidated. Our study aimed to detect the effect of amino acids and processing methods on the conversion of ginsenosides in American ginseng to rare ginsenosides, using 8 monomeric ginsenosides as substrates to discuss the reaction pathway and mechanism. S180 tumour-bearing mice were established to study the antitumour effects of American ginseng total saponins (AGS-Q) or American ginseng total saponins after transformation (AGS-H) synergistic CTX. The results showed that aspartic acid was the best catalyst, and the thermal extraction method had the best effect. Under the optimal conditions, including a reaction temperature of 110℃, an aspartic acid concentration of 5%, a reaction time of 2.5 h and a liquid-solid ratio of 30 mL/g, the highest conversion of Rk1 and Rg5 was 6.58±0.11 mg/g and 3.74±0.05 mg/g, respectively. In the reaction pathway, the diol group saponins participated in the transformation process, and the triol group saponins basically did not participate in the transformation process. AGS-Q or AGS-H synergistic CTX, or AGS-H synergistic CTX/2 could significantly increase the tumour inhibition rate, spleen index and white blood cell count, had a significant upregulation effect on IL-2 and IL-10 immune cytokines; significantly restored the ratio of CD4+/CD8+; and significantly inhibited the level of CD4+CD25+. AGS-Q or AGS-H synergistic with CTX or CTX/2 can significantly upregulate the expression of Bax and cleaved-Caspase-3 and inhibit the expression of antiapoptotic protein Bcl-2. AGS synergistic CTX in the treatment of S180 tumour-bearing mice can improve the efficacy and reduce toxicity.